Successful intraosseous adenosine administration in a newborn infant with supraventricular tachycardia - Fidancı, İlknur and Güleryüz, Okşan Derinöz and Yenice, Ömer Doğan (The Turkish Journal of Pediatrics, 2020)
Background. Supraventricular tachycardia (SVT) is the most common type of tachycardia in childhood. The incidence is 1-4/1000 in childhood and 0.6/1000 in newborns. Case. Here we report a 28-day-old male newborn who was diagnosed SVT, admitted to the Pediatric Emergency Department after restlessness that had started three hours before admission and measurement of the heart rate was above 250 beats/min. Conclusions. This case is presented in order to emphasize that SVT is rare in the neonatal period and SVT is successfully terminated with the administration of intraosseous adenosine.